Заповідна екзотична дендросозофлора EX SITU зони широколистяних лісів України (аналіз структури, репрезентативність культування, фітоценодизайн - Міськевич, Лариса Вікторівна (НУБіП України, 2018)
Дисертація на здобуття наукового ступеня кандидата біологічних наук зі спеціальності 06.03.01 «Лісові культури та фітомеліорація». Національний університет біоресурсів і природокористування України. Київ, 2018. Дисертацію присвячено дослідженню заповідної екзотичної дендросозофлори ex situ зони широколистяних лісів України, її систематичному, біоморфологічному, географічному, екологічному, фітоценотипному й аутфітосозологічному аналізу. Установлено кількісний і якісний склад її структури, у тому числі вікових дендросозоекзотів. У дисертації вперше виокремлено періодизацію паркобудівництва у межах зони широколистяних лісів України; здійснено комплексний структурний аналіз заповідної екзотичної дендросозофлори; проаналізовано флористичний склад вікових дендросозоекзотів; з’ясовано сучасний стан репрезентативності культивування досліджених видів рослин; установлено результати успішності їхньої інтродукції, здійснено оцінку декоративності дендросозоекзотів; розроблено практичні рекомендації щодо поповнення колекцій установ природно-заповідного фонду раритетними дендроекзотами та їх використання у ландшафтному фітоценодизайні
The thesis for awarding a scientific degree of candidate of biological sciences in specialty 06.03.01 «Forest Plantations and Phytomelioration». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2018. The thesis is devoted to research of rare exotic dendrosozoflora ex situ of broadleaf forests zone of Ukraine, its systematic, biomorphological, geographical, ecological, phytocenotic and autphytosozological analyses. It is revealing the quantitative and qualitative composition of its structure including age-old dendrosoexots, for the Nature Reserve Fund, of the broadleaved forest zone of Ukraine. In the process of analysis of taxonomical structure of rare exotic dendrosozoflora of artificial protected park and garden objects it is educed that rare dendrodiversity counts 176 species of wood plants. The most numerous department is Pinophyta (102 species), that includes six families. Magnoliophyta has 74 (42 %) species. The most representative families in this department are Betulaceae – 16 (9.4 %) species, Magnoliaceae and Rosaceae have 13 species. During biomorphological structure research it is set, that dendroexots belong to four group of life-form, namely trees (154 species), shrubs (20 species), semi-shrubs (one species) and arboreal lianas (one species). In the group of trees dominated by evegreen plants (86 species), from the deciduous plants, 68 species were identified. The type of shrubs consists of nine evegreen and 11 deciduous. The type of shrubs represents only one evegreen species. According to the classification of life forms of plants C. Raukier, rarite dendroexcolds are phanerophytes. Depending on their height, they are divided into: megafanerophytes, mesophanephrosis, microfanerophytes and nanofanerophytes. The most representative species is the mesophanephoritis group, which includes 87 rare dentists, of which 43 are the Pinophyta and 44 are Magnoliophyta. Megafanerophytes include 56 species, of which predominant rare are dendroexots from the Department of Pinophyta. From Magnoliophyta, only seven species belong to this group. Microfanerophytes have 19 species. In this group, the majority are shrouded dendrosozoexots. To gymnosperms microfanerophytes belong to four types. Nanophanerophytes are represented by 14 rare dendroexots. Depending on a height, rare dendroexots are divided into groups D1, D2, D3, D4. A group D1 prevails after the amount of wood plants species and includes 78 species. After the classes of height shrubs are divided into subzero – seven species, middle – eight species and high – five species. As a result of floristic analysis it is educed, that dendroexots take place from 11 floristic regions. The natural habitat of most investigated species is East-asian floristic area that presents 42 species (23.9 %). On results research of ecological structure of rare exotic dendroflora prevailing on the quantity of species are such ecogroups: mesophytes – 69 species, among that majority is presented to the dendroexots department of Pinophyta – 42 species (23.9 %); heliophytes count 81 species (44 deciduous and 37 gymnosperms species); mesophytes present 83 rare species of wood plants from a general amount species, in this group will outweigh gymnosperms dendroexots and count 44 species; microtherms in investigational dendrosozoflora are presented by 101 species (64 gymnosperms and 37 angiosperms species). Transitional ecological groups present the negligible quantity of species. Analysis of phytocenotic structure showed, that rare dendrodiversity presented by the species, which are assectants, dominants, co-dominants and edificators. Majority of dendroexots are assectants (38 species) and co-dominants (21 species), 16 types of digitizers. In the group of assectants, dendrososoexotic is dominated by Magnoliophyta – 33 species; in the group of dominants and co-dominants, the majority are rare species of woody plants from the Department of Pinophyta. As a result of autphytosozological analysis it is educed, that 96 % rare dendroexots protected by the Red List of International Union for Conservation of Nature and Natural Resources, two species belong to European Red List (Forsythia europaeа Degen et Bald. and Spiraea cana Waldst. & Kit.), one species protected by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (Quercus mоngоlica Fisch. ex Ledeb.), three species belong to European Red List and the Red List of International Union for Conservation of Nature and Natural Resources – Picea omorica (Panc.) Purkyne, Abies pinsapo Boiss. and Pyrus salicifolia Pall. Araucaria aruacana (Mol.) C. Koch. protected by the Red List of International Union for Conservation of Nature and Natural Resources and by addition of Convention on International Trade in Endangered Species of Wild Fauna and Flora. There are 125 species are under a small threat. Some dendroexots are under critical threat of disappearance: Betula kirghisorum Sav.-Ryczg., Metasequoia glyptostroboides Hu & W. C. Cheng, Thuja sutchuenensis Franch. and Betula schugnaninica (B. Fedtsch.) Litv. Floristic composition of age-old dendroexots is analysed and educed that on the naturally-protected territories and artificial protected parks of broadleaf forests zone of Ukraine are counted 34 species of age-old rare dendroexots ex situ. The species of department of Pinophyta prevail on a quantity. The most amount of rare dendroexots are presented in the botanical gardens – 161 species, 115 species are educed on territories of dendrology parks, the parks of sight of park and garden art count 70 species, five kinds are counted in zoological park. The most amount (94 species) of dendroexots are in the Botanical garden of Ivan Franko Lviv National University. Among the dendrological parks, the largest number of rare species of woody plants has the Germanic – 86 species. In parksmemorials of landscape gardening found much less dendrosozoexots. The richest rare dendrodiversity was found in park-memorial of landscape gardening «Rivne Park named after TG Shevchenko», which has 28 species. Rare dendroexots are belong two decorative groups: highly decorative and medium decorative. The highest number of highly decorative dendrosozoexots was found in the Department of Pinophyta. The highest scores (32–34) were Magnolia grandiflora, Magnolia kobus and Abies veitchii, while the lowest (19–22 points) were Ostrya carpinifolia, Ficus carica and Sibiraea altaiensis
Keywords: зона широколистяних лісів України; раритетні дендроекзоти; природно-заповідний фонд; ex situ; Червоний список Міжнародного союзу охорони природи та природних ресурсів; репрезентативність; успішність інтродукції; декоративність; штучні заповідні парки; broadleaf forests zone of Ukraine; rare dendroexotics; Nature Reserve Fund